1996
DOI: 10.1172/jci118945
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against CD14 protect primates from endotoxin-induced shock.

Abstract: Lipopolysaccharide (LPS), residing in the outer membrane of all gram-negative bacteria, is considered a major initiating factor of the gram-negative septic shock syndrome in humans. LPS forms a complex with the LPS binding protein (LBP) in plasma, and LPS-LBP complexes engage a specific receptor, CD14, on the surface of myeloid cells, leading to the production of potent proinflammatory cytokines. The major goal of this study was to test the importance of the CD14 pathway in vivo in a primate model that is simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
2
5

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(94 citation statements)
references
References 32 publications
8
79
2
5
Order By: Relevance
“…Our results may appear inconsistent with earlier studies that demonstrated that animals lacking CD14 or treated with a CD14-specific mAb are protected against endotoxin-mediated shock (12,15). These divergent results are probably due to the fact that those earlier studies employed purified LPS or bacteria that were administered systemically, whereas we used live bacteria that were deposited on a mucosal surface.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results may appear inconsistent with earlier studies that demonstrated that animals lacking CD14 or treated with a CD14-specific mAb are protected against endotoxin-mediated shock (12,15). These divergent results are probably due to the fact that those earlier studies employed purified LPS or bacteria that were administered systemically, whereas we used live bacteria that were deposited on a mucosal surface.…”
Section: Discussioncontrasting
confidence: 99%
“…Primates that were treated with monoclonal anti-CD14 Ab i.v. did not develop endotoxic shock after LPS infusion (15). Anti-CD14 treatment also protected rabbits from organ injury and death elicited by repeated administration of LPS i.v.…”
Section: Blockade Of Cd14 Increasesmentioning
confidence: 86%
“…Inhibition of the CD14 pathway represents an experimental method to prevent septic shock (Leturcq et al 1996) in primates and rabbits (Schimke et al 1998). The administration of CD14-antibodies was effective in preventing septic shock even when administered after LPS exposure.…”
Section: Membrane-associated Moleculesmentioning
confidence: 99%
“…The crucial role of CD14 in LPS signaling has been confirmed with knock-out mice; CD14-deficient mice are highly resistant to septic shock initiated by injection of either LPS or live bacteria (11). The CD14 pathway has been suggested as a therapeutic target because anti-CD14 monoclonal antibodies gave significant protection against septic shock in animal models (12,13). In addition to the LPS of Gram-negative bacteria, CD14 can bind other microbial products such as peptidoglycan (PGN), lipoteichoic acid, lipoarabinomannan, and lipoproteins (14,15).…”
mentioning
confidence: 99%